2019
DOI: 10.1021/acs.joc.9b02615
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation near a Patch of Nonpolar Surface Residues Increases the Conformational Stability of the WW Domain

Abstract: Many proteins have one or more surface-exposed patches of nonpolar residues; our observations here suggest that PEGylation near such locations might be a useful strategy for increasing protein conformational stability. Specifically, we show that conjugating a PEG-azide to a propargyloxyphenylalanine via the copper­(I)-catalyzed azide–alkyne cycloaddition can increase the conformational stability of the WW domain due to a favorable synergistic effect that depends on the hydrophobicity of a nearby patch of nonpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In this case, the optimal increase in proteolytic stability was linked with a conformational stability high increase. Furthermore, they found the (identity dependent linker between PEG and protein) alternative PEGylation strategies which effectively alters the WW protein conformational stability [22]. The location, length of PEG, and chemistry used 3 BioMed Research International to connect PEG with proteins may influence conformation stability.…”
Section: Site-specific Protein Pegylation Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the optimal increase in proteolytic stability was linked with a conformational stability high increase. Furthermore, they found the (identity dependent linker between PEG and protein) alternative PEGylation strategies which effectively alters the WW protein conformational stability [22]. The location, length of PEG, and chemistry used 3 BioMed Research International to connect PEG with proteins may influence conformation stability.…”
Section: Site-specific Protein Pegylation Strategiesmentioning
confidence: 99%
“…PEGylation at the N-terminal did not substantially change the stability of SH3 [ 21 ]. Residue specific PEGylation was shown to strengthen the Glu12-Arg14 salt-bridge by shielding it from the interference of water molecules [ 22 ]. Recently, Zuma and colleagues (2022) recently demonstrated that site-specific PEGylation enhances the biological activity and stability of recombinant DNA ligase proteins [ 23 ].…”
Section: Site-specific Protein Pegylation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rational design guidelines are needed to drive forward such optimizations , and pave the way for viable, biocompatible PEG alternatives. Therefore, a thorough understanding of the underlying protein–polymer structure and its dynamics is crucial. Unfortunately, harnessing the full potential of the typical experimental approaches used in structural biology, such as X-ray crystallography, cryo-electron microscopy and nuclear magnetic resonance (NMR) spectroscopy, is inherently difficult for bioconjugates with their highly flexible polymer chains. Experimental investigations into protein–polymer dynamics mainly rely on stability data obtained from systematic mutation studies, deducing structure–function–dynamics relationships indirectly. Alternative techniques have been reported, such as hydrogen–deuterium exchange experiments, small-angle neutron or X-ray scattering (SANS/SAXS), , spin labeling of polymers for subsequent NMR measurements and limited-proteolysis (LiP) assays …”
Section: Introductionmentioning
confidence: 99%